Haploidentical stem cell transplantation with posttransplant cyclophosphamide in children with Wiskott–Aldrich syndrome: a case report - Nguyen Ngoc Quynh, Le; Nguyen Thanh, Binh; Luong Thi, Lien; Nguyen Thi Dieu, Thuy; Dang Anh, Duong; P. Lee, Pamela; Cao Viet, Tung; Tran Minh, Dien (Frontiers in Immunology, 2025)
Wiskott–Aldrich syndrome (WAS) is a condition characterized by a low platelet count, eczema, and a weakened immune system. Hematopoietic stem cell transplantation (HSCT) is the only curative treatment option. Haploidentical HSCT with posttransplant cyclophosphamide (PTCy) is an emerging approach for children with noncancerous conditions. This case describes a WAS patient who was early diagnosed and successfully treated with haploidentical HSCT. A 3-month-old boy presented with widespread eczema, a low platelet count, and severe infections in infancy. The diagnosis of WAS was quickly confirmed by genetic test. He received immunoglobulin replacement therapy and antimicrobial prophylaxis and underwent HSCT at 4 years 3 months of age. After failed unrelated cord blood HSCT, second rescue haploidentical HSCT had been performed using the patient’s mother as the donor, with stem cells collected from peripheral blood. The conditioning regimen included anti-thymocyte globulin, melphalan, and fludarabine. The stem cell dose was 2.63 × 106 CD34+ cells/kg. GVHD prevention included PTCy, mycophenolat mofetil, and tacrolimus. The patient had no significant complications after the transplant. Neutrophil and platelet engraftment occurred promptly. At 32 months post-HSCT, the patient had complete hematological and immune reconstitution, with full donor chimerism and no GVHD. In conclusion, the PTCy approach to haploidentical HSCT was a safe and effective treatment for this WAS patient.